Marrow fat composition in anorexia nervosa - Bredella, Miriam A. (2014)
PURPOSE: Women with anorexia nervosa (AN) have increased marrow fat despite severe depletion of body fat. Recent studies have suggested that marrow fat composition may serve as a biomarker for bone quality. The purpose of our study was to investigate marrow fat composition of the femur using proton MR spectroscopy (1H-MRS), and the relationship between measures of marrow fat composition and BMD and body composition in women with AN and normal-weight controls. MATERIALS AND METHODS: 14 women with AN (29.5±1.9 years) and 12 age-matched normal-weight controls underwent 1H-MRS to determine total marrow fat content and marrow fat composition of the femoral diaphysis and soleus intramyocellular lipids und unsaturated muscle lipids. MRI was performed to quantify abdominal fat, thigh fat and muscle. Lumbar spine BMD, fat and lean mass were assessed by DXA. RESULTS: Subjects with AN had higher marrow fat content (p<0.05), but similar marrow fat composition (p >0.05) compared to normal-weight controls. There was an inverse association between marrow methylene protons, an estimate of fatty acid (FA) saturated bonds, and lumbar spine BMD (r= -0.52, p=0.008) independent of %ideal body weight (%IBW). Olefinic protons at 5.3 ppm, an estimate of FA unsaturated bonds, were inversely associated with body fat depots, independent of %IBW, and positively associated with soleus unsaturation (p≤0.05). CONCLUSION: Women with AN have higher total femoral marrow fat but similar composition compared to normal-weight controls. The degree of marrow FA saturation correlates inversely with BMD, suggesting that saturated lipids may have negative effects on BMD. The degree of marrow FA unsaturation correlates positively with soleus unsaturation, suggesting that marrow fat composition may be influenced by the same factors as ectopic lipid composition in muscle.